Os novos aspectos da decisão saneadora - Pavoni, Mariana Melo de Carvalho (2019)
The present dissertation focuses on the current aspects of the pre-trial decision, its characteristics, legal nature, its purpose and, in addition, its usefulness to the civil procedural system. As will be demonstrated in this study, the pre-trial decision is not a new doctrine nor a new concept in Brazilian legal system, although it has undergone modifications, which, in our understanding, was for the better. The pre-trial decision doctrine evolved in the current civil procedural law and gained greater scope and robustness. In the current Civil Procedure Code, the preliminary questions, whose decision will become final and unappealable, will depend exclusively on the corrective decision. As well as lis pendens regarding to these matters. Nowadays, since the new Civil Procedure Code, the first instance judge will determine which of the preliminary ruling are able to be final and unappealable, and this definition will be taken at the order. It will be demonstrated in this dissertation that the conclusive opening order will stabilize and will be a definite boundary for the judge who issued it, which once again emphasize the importance of the order and the impossibility that this decision is limited, merely, to a declaratory content. The parties play a fundamental role in the pre-trial decision, largely because of the important participation of them in the search for the truth regarding the procedure, through an efficient evidence finding and evidentiary phase. The corrective decision gained great importance and new boundaries. It now defines the course of the procedure. Therefore, the present study intends to better understand this well-known judicial pronouncement